Commons Tenure for a Common Future - Meinzen-Dick, Ruth S. (2015)
Presentation by Ruth Meinzen-Dick, Head of Collection Action and Property Rights (CAPRi) Research Program, and Senior Research Fellow in the Environment, Production, Technology Division (EPTD) at the International Food Policy Research Institute (IFPRI), at the Global Landscapes Forum on December 5, 2015 in Paris, France.